Model Mediasi Berbasis Maqāṣid al-Syarī‘ah dalam Penyelesaian Konflik Rumah Tangga - Era Zufialina; Ahmad Syafruddin (Lembaga Yasin AlSys, 2026)
Family conflicts often arise from interconnected psychological, economic, communication, and violence-related factors, while conventional mediation models are often procedural and less sensitive to emotional inequality and power relations. This study aims to formulate a mediation model for resolving family conflicts based on the principles of maqāṣid al-syarī‘ah. This study used a qualitative descriptive method with a normative-analytical approach through an analysis of classical uṣūl al-fiqh literature, contemporary studies, and Perma No. 1/2016 regulations. The results show that the integration of the five objectives of maqāṣid, namely the protection of religion, life, intellect, lineage, and property, provides a substantive ethical foundation for a mediation process that emphasizes justice, safety, and the sustainability of agreements. The Islamic family mediation model is formulated in four systematic stages, namely pre-mediation through self-assessment and emotional readiness, mediation implementation through maslahat–mafsadat assessment and empathetic communication, agreement formulation through justice-based validation, and post-mediation monitoring oriented toward child protection and the continuity of agreements. The conclusion of this study affirms that the maqāṣid al-syarī‘ah-based mediation model is more responsive, humane, and relevant in addressing the complexity of modern family conflicts. The contribution of this study lies in the formulation of an operational framework for Islamic family mediation that integrates normative, ethical, and practical dimensions to strengthen conflict resolution within families and religious court institutions.